2020
DOI: 10.1002/for.2691
|View full text |Cite
|
Sign up to set email alerts
|

Cryptocurrency volatility forecasting: A Markov regime‐switching MIDAS approach

Abstract: The primary purpose of this paper is to investigate whether a novel Markov regime-switching mixed-data sampling (MRS-MIADS) model we design can improve the prediction accuracy of the realized variance (RV) of Bitcoin. Moreover, to verify whether the importance of jumps for RV forecasting changes over time, we extend the standard MIDAS model to characterize two volatility regimes and introduce a jump-driven time-varying transition probability between the two regimes. Our results suggest that the proposed novel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 52 publications
(25 citation statements)
references
References 68 publications
1
22
0
Order By: Relevance
“…especially in the Bitcoin, Ether and Litecoin cryptocurrency markets. Further, Ma et al (2020) found that the proposed novel MRS-MIDAS model exhibits statistically significant improvement for forecasting the RV of Bitcoin Between 2011 and 2018, Adcock and Gradojevic (2019) found that backpropagation neural networks dominate various competing models in terms of their forecast accuracy. Further, when attempting to predict Bitcoin bubble crashes, Shu and Zhu (2020) showed that an LPPLS confidence indicator presented superior detection capability to bubbles and accurately forecast the bubble crashes, even if a bubble existed for only a short period of time.…”
Section: Previous Literaturementioning
confidence: 96%
“…especially in the Bitcoin, Ether and Litecoin cryptocurrency markets. Further, Ma et al (2020) found that the proposed novel MRS-MIDAS model exhibits statistically significant improvement for forecasting the RV of Bitcoin Between 2011 and 2018, Adcock and Gradojevic (2019) found that backpropagation neural networks dominate various competing models in terms of their forecast accuracy. Further, when attempting to predict Bitcoin bubble crashes, Shu and Zhu (2020) showed that an LPPLS confidence indicator presented superior detection capability to bubbles and accurately forecast the bubble crashes, even if a bubble existed for only a short period of time.…”
Section: Previous Literaturementioning
confidence: 96%
“…[ 60 ] and Ma et al. [ 37 ]; we apply recursive (expanding) estimation window to do the evaluation, which can minimize loss of freedom and protect the original data information as much as possible. The results of recursive (expanding) estimation window are presented in Table 10 .…”
Section: Empirical Designmentioning
confidence: 99%
“…Moreover, the centralized exchanges finance cannot provide the high transparency, as centralized financial institutions have to secure their centralized ledgers by restricting access (Chen & Bellavitis, 2020). Previous studies on the centralized exchanges platform are focused on the price discovery (Patel et al, 2020;Alexander et al, 2020), risk exposure analysis (Corbet et al, 2020;Brauneis & Mestel, 2019), cryptocurrency volatility (Conrad et al, 2018;Walther et al, 2019;Bouri et al, 2019;Ma et al, 2020).…”
Section: Introductionmentioning
confidence: 99%